THE INFLUENCE OF PSYCHOSOCIAL DEVELOPMENT ON THE LEARNING RESPONSIBILITY OF SCHOOL-AGED CHILDREN - Ermalia Mutiara; Hamiyati; Hurriyyatun Kabbaro (JKKP (Jurnal Kesejahteraan Keluarga dan Pendidikan), 2024)
Abstract Psychosocial development that is not fully mature can impact the learning responsibility of school-aged children. This study aims to analyze the influence of psychosocial development on the learning responsibility of school-aged children. Data was collected using the cluster random sampling technique. The research sample consisted of 172 fifth and sixth-grade students from one school in Bekasi city and two schools in Bekasi Regency. Data collection was conducted using a questionnaire. The instrument used to measure psychosocial development consisted of 19 items based on the dimensions of industry and inferiority. The instrument used to assess learning responsibility consisted of 22 items based on the dimensions of learning responsibility during the course and learning responsibility outside the course. The collected data was processed and analyzed using descriptive and inferential statistics, specifically simple linear regression tests. The results of the study showed that psychosocial development positively influences learning responsibility. The determination coefficient obtained was 0.496%, meaning that psychosocial development affects learning responsibility by 49.6%, while the remaining 50.1% is influenced by other factors. Therefore, it is essential for involved parties to be aware of children's psychosocial development to enhance their learning responsibility. Abstrak Perkembangan psikososial yang belum matang sepenuhnya dapat memengaruhi tanggung jawab belajar anak usia sekolah. Penelitian ini bertujuan untuk menganalisis pengaruh perkembangan psikososial terhadap tanggung jawab belajar anak usia sekolah. Data dikumpulkan menggunakan teknik cluster random sampling. Sampel penelitian terdiri dari 172 siswa kelas V dan VI dari satu sekolah di Kota Bekasi dan dua sekolah di Kabupaten Bekasi. Pengumpulan data dilakukan menggunakan kuesioner. Instrumen yang digunakan untuk mengukur perkembangan psikososial terdiri dari 19 butir berdasarkan dimensi industri dan inferioritas. Instrumen yang digunakan untuk menilai tanggung jawab belajar terdiri dari 22 butir berdasarkan dimensi tanggung jawab belajar selama pembelajaran dan tanggung jawab belajar di luar pembelajaran. Data yang terkumpul diolah dan dianalisis menggunakan statistik deskriptif dan inferensial, khususnya uji regresi linear sederhana. Hasil penelitian menunjukkan bahwa perkembangan psikososial berpengaruh positif terhadap tanggung jawab belajar. Koefisien determinasi yang diperoleh sebesar 0,496%, yang berarti perkembangan psikososial memengaruhi tanggung jawab belajar sebesar 49,6%, sedangkan sisanya 50,1% dipengaruhi oleh faktor lain. Oleh karena itu, penting bagi pihak terkait untuk memperhatikan perkembangan psikososial anak guna meningkatkan tanggung jawab belajarnya.